The musical rhetoric of charismatic revival: continuity and change in the songs of the Toronto Blessing and Bethel Church - Baker, Shannan K.; Ingalls, Monique 1981- (2022)
Renewal movements like the Toronto Blessing and the signature form of ‘encounter’ offered at Bethel Church influence Pentecostal practice worldwide. Songs from these movements reverberate widely, serving as portable practices that help to carry the message and experience of renewal to new settings. Increasingly, scholars are paying attention to song lyrics as sources of Pentecostal theologies; likewise, ethnographic accounts have provided key insights into how the activity of singing during renewal worship shapes participants’ experience. What is often missing from scholarly accounts, however, are the songs themselves; in other words, the irreducible textual-musical units that display integrity across performance contexts. In analyzing a body of North American renewal songs spanning from the mid-1990s to the present day, this study set forth a method to study the music of Pentecostal renewal songs. Building from and augmenting previous studies of revival song lyrics, we argue that certain themes, such as love and elemental metaphors, and different uses of pronouns referring to both God and one another are central for understanding the efficacy of renewal songs.
Keywords: Bethel Church; Contemporary worship; Pentecostal-charismatic music; Toronto Blessing; Metaphor; Revival